Decolorization of azo dyes in sequencing batch reactor - Tapas, Arturo L. Jr. (2007)
A synthetic wastewater was prepared to simulate actual dye wastewater. The azo dyes used were C.I. reactive Red 141 and methyl orange. C.I. Reactive Red 141 is typical of those dyes with persistent colors in the textile industry effluent discharges. The COD of the synthetic wastewater was adjusted by the addition of sucrose. The dye the primary substrate was decolorized in the presence of sucrose which was the supplementary substarte. The azo dyes were decolorized largely during the unaerated mixing in the sequencing batch reactor (SBR), decolorization during aerated (aerobic) mixing was much less. The sludge used in the SBR was from the aerotion tank of the STP of the Manila Sewage Treatment Plant in Philocoa, Quezon City (Sludge A) and another one developed by the aeration of sewage under acidic condition (Sludge B). The BR was operated with alternating unaerated and aerobic conditions in the react event of the SBR, During unaerated conditions the azo dyes were cleaved into two animes resulting to decolorization; these two amines as well as the otherproducts of anerobic decomposition were then mineralized in the subsequent aeration. Substantial decolorization of C.I. Reactive Red 141 was attained using Sludge A if basic condition was maintained in the reactor. Sludge B was not effective in decolorization of this dye. Substantial decolorization of methyl orange was attainable at both basic and acidic conditions using sludge A or Sludge B.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Azo dyes